COP27 Growing Roles for Agriculture and Food Security - Witkowski, Kelly (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Agriculture has not had a significant presence in the national and international climate processes. Yet as COP27 ended there was a strong push by many public, private and civil society actors for agriculture to have a stronger presence and voice. Increased visibility also came from a number of the first ever agriculture and food-focused pavilions.There is still a long way to go to ensure the progress benefits the world’s farmers.What remains to be done? The quantity and quality of climate finance needs to improve and be better directed; and agriculture and food security need to be front and center in the discussion and in tangible climate action—and also in it for the long game.